Lurking Within Reach: Stereoscopic Photomicrography in the 1860s - Wasielewski, Amanda (History of photography, 2015)
In the 1860s, the debate over whether photography was an accurate and useful tool for recording microscopic specimens was unresolved. Albert Moitessier's La photographie appliquée aux recherches micrographiques (1866) was one of the first instructional books to outline techniques combining photography and microscopy. Moitessier was unique among his contemporaries in his emphasis on stereoscopy and binocular vision. This essay addresses questions arising from Moitessier's unusual inclusion of a stereograph in his plates and his description of stereoscopic techniques in his text. While an ordinary photomicrograph renders the invisible microscopic world visible, the stereoscope brings this intangible realm within reach. The stereoscope is imbued, in this context, with a unique machinic vision as well as a haptic faculty that supersedes human perceptual ability. The apparent objectivity these extra-human capabilities facilitate, in turn, lends autonomy to stereo-photomicrographic tools. As the gulf between human and machine perception widens, the spectre of artificial intelligence grows, contributing to the disorientation in the nineteenth century over an expanded sense of existence.